DOI: 10.31274/rtd-180813-13628
|View full text |Cite
|
Sign up to set email alerts
|

Soybean yield, yield components, seed quality, dehydrin-like proteins, soluble sugars, and mineral nutrients in response to drought stress imposed prior to severe stress

Abstract: Drought stress reduced soybean seed yield, but its effect on seed quality was highly variable. Two greenhouse experiments (one in summer and one in winter) and one field experiment were conducted to investigate the effects of drought pre-conditioning on seed yield, size, quality, accumulation of dehydrin-like proteins and soluble sugars in relation to seed quality, and seed mineral nutrients. In summer, soybean {Glycine max L.) plants were exposed at beginning seed fill (R5) to well-watered (WW), sudden stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 99 publications
(205 reference statements)
0
1
0
Order By: Relevance
“…Du et al [13] found that drought prevailing during generative stage, mainly at the middle and late seed filling phases, sucrose movement from leaves to seeds was lessen, and the balance of sucrose metabolism was defected in seeds, rendering in seed mass reduction. Number of full pods per plant and seed size are main attributes of soybean seed yield, the higher the number and the larger the seed size, the higher the yield [14,15,16].…”
Section: Resultsmentioning
confidence: 99%
“…Du et al [13] found that drought prevailing during generative stage, mainly at the middle and late seed filling phases, sucrose movement from leaves to seeds was lessen, and the balance of sucrose metabolism was defected in seeds, rendering in seed mass reduction. Number of full pods per plant and seed size are main attributes of soybean seed yield, the higher the number and the larger the seed size, the higher the yield [14,15,16].…”
Section: Resultsmentioning
confidence: 99%